Plastics underground: microplastic pollution in South African freshwater caves and associated biota - Thendo Mutshekwa; Samuel N. Motitsoe; Trishan Naidoo; Zamabhisi Majingo; Musa C. Mlambo (Hydrobiologia, 2026)
Microplastics (MPs) have been characterised in South African rivers, lakes, and the marine environment, yet we know less about MPs in subterranean environments. In this study, we assessed MP pollution in the sediment, subsurface water, and resident freshwater amphipod, Sternophysinx species across six South African subterranean cave systems. We hypothesised that MP pollution will increase with human visitations and activities in and around selected subterranean caves. We found MPs in sediments, subsurface waters, and amphipod species ranging from 4.9 ± 1.2 to 25.0 ± 6.9 particles/kg –1 , 2.7 ± 0.7 to 15.0 ± 1.7 particles/L –1 and 2.1 ± 0 to 9.8 ± 3.1 particles/dry mass, respectively, with polypropylene being the most abundant polymer according to FTIR analysis. White fibres were dominant in sediments and water samples, whereas blue fibres were dominant in amphipods. Our results supported the hypothesis that MPs densities were correlated with human visitation and activities in and around the caves. The presence of MPs in subterranean caves presents a biodiversity and conservation threat to endemic and understudied cave-dwelling aquatic invertebrates, due to MPs ability to be transferable between trophic levels causing physiological constraints.

Plastic Particles in Pristine Waters? Investigating Microplastic Contamination in Natural Springs - Thendo Mutshekwa; Musa C. Mlambo; Trishan Naidoo; Sive Kolisi; Oghenekaro N. Odume; Rabelani Mudzielwana; Samuel N. Motitsoe (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern, particularly in freshwater systems. However, little is known about the occurrence and characteristics of MPs in groundwater-fed freshwater sources such as natural springs. In this study, the presence, abundance and characteristics of MPs were investigated in freshwater natural springs across South Africa, representing different land-use types (i.e. rural and peri-urbanl) and spring type (i.e. modified and unmodified). On average, 6 particles per L (± 1.2 SD) of MPs were recorded, ranging between 2 (limit of quantification; LOQ) to 38 particles per L. Land-use and spring type did not show any significant influence on MPs abundance ( p > 0.05). Overall, MPs exhibited diverse characteristics. Fibres (67.8%) were the predominant shape, while blue (28.8%) was the most common colour. The dominant size class was 100–250 µm across all springs, while the dominant polymer was polyethylene (PE; 46.8%). Our findings suggests that groundwater-fed water sources like natural springs, regardless of their limited exposure to above ground environment, are equally at risk of MPs contamination, similar to surface freshwater systems. This research provides empirical evidence on MPs contamination and monitoring of remote ecosystems, highlighting the ecological and social risk of MPs pollution in important freshwater resources. The study contributes valuable data for understanding MP dynamics including their densities and sources from groundwater-fed freshwater resources, offering insights into broader environmental pollution to African systems.

Unravelling the long-term river health status of Kruger National Park Rivers using macroinvertebrate-based monitoring - Hendrik Sithole; Samuel N. Motitsoe; Thendo Mutshekwa; Musa C. Mlambo (Environmental Monitoring and Assessment, 2025)
The burgeoning population growth and landscape developments over the last decades have had a profound effect on natural resources including riverine water quality and quantity. This resulted in increased pollution events, loss of aquatic biodiversity and the introduction of alien invasive species, which cumulatively have transformed freshwater ecosystem structure, processes and functions. Macroinvertebrate-based biomonitoring, like the South African Scoring System version 5 (SASS5), is a fast and effective way to assess water and habitat quality. However, studies reporting long-term biomonitoring are rare in many Global South systems. Also, river health within protected areas is generally regarded better than those outside, with the park potentially offering refugium and ideal conditions for rivers to recover. However, Kruger National Park (KNP) rivers get impacted by mining and domestic sewage upstream, before entering the park, and it is not clear how much remediation happens as the rivers flows downstream within the park. The current study was initiated to investigate the long-term river health status of four major river systems flowing across the iconic KNP, using SASS5 biomonitoring and selected physico-chemical parameters. Our results showed that SASS5 indices showed difference in their sensitive to anthropogenic impacts, both in space and time. Long-term dataset revealed that the ability of the rivers to recover from poor to good quality (and vice versa) was quite rapid, and also some rivers were progressively declining (e.g. Olifants and Crocodile rivers) while others were improving (e.g. Luvuvhu and Sabie rivers). Consequently, SASS5 appeared to be a useful tool in assessing the long-term health of KNP rivers, providing valuable insights into the overall ecological conditions and water quality of these important aquatic ecosystems that will assist in the park water resource management strategies. Further, our results demonstrated high sensitivity and quick response of macroinvertebrates to disturbance, and an improvement potential as the rivers transversed the park.

Does Perceived Nuisance Abundance of Water Plants Match with Willingness-to-Pay for Removal? Contrasts Among Different User Categories - Jan E. Vermaat; Kirstine Thiemer; Bart Immerzeel; Susanne C. Schneider; Keneilwe Sebola; Julie Coetzee; Antonella Petruzzella; Samuel N. Motitsoe; Mathieu Baldo; Benjamin Misteli; Gabrielle Thiébaut; Sabine Hilt; et al. (Environmental Management, 2025)
Dense beds of water plants can be perceived as nuisance, but this perception, however, may not be similar for different user categories, and this may affect their willingness-to-pay (WTP) for plant removal. A questionnaire survey was used to test this for residents and visitors and find underlying socio-cultural or economic drivers. We studied five cases where nuisance water plant growth is managed: the rivers Otra (Norway) and Spree (Germany), and the lakes Kemnade (Germany), Grand-Lieu (France), and Hartbeespoort Dam (South Africa). We used a different payment vehicle for residents (annual household tax) and visitors (tourist tax). The survey included questions on days spent on specific types of activity per year, the importance attached to different functions and activities, overall environmental attitude, perception of the plants, socio-demographic respondent characteristics and WTP for increased plant removal. We observed no increase in WTP for increased removal in most sites. The two most important drivers of variation in current WTP were income, and whether respondents were engaged in boating and angling and thus perceived the plants negatively. Variation in WTP among sites was considerable, and mainly related to the mixture of activities among respondents. Differences between residents and visitors were less important than those among sites. Our observations bear importance for water management: information on differences in experienced nuisance among user categories and the frequency of use by these categories is useful as guidance for the design and implementation of any plant removal plan.

Causes of macrophyte mass development and management recommendations - Susanne C. Schneider; Julie A. Coetzee; Elena Fukasawa Galvanese; Sarah Faye Harpenslager; Sabine Hilt; Bart Immerzeel; Jan Köhler; Benjamin Misteli; Samuel N. Motitsoe; Andre A. Padial; Antonella Petruzzella; Anne Schechner; et al. (Science of The Total Environment, 2024)

Recent post-release evaluations of weed biocontrol programmes in South Africa: a summary of what has been achieved and what can be improved - Iain D. Paterson; Samuel N. Motitsoe; Julie A. Coetzee; Martin P. Hill (BioControl, 2024)
Biocontrol is widely considered an effective management solution for mitigating the negative impacts of invasive alien plants (weeds). Globally, post-release evaluations to assess individual biocontrol programmes are generally lacking and there have been persistent calls within the biocontrol of weeds literature to increase the quantity and quality of post-release evaluation studies. South African biocontrol researchers have prioritised post-release evaluation studies, with a significant proportion of funding dedicated to this purpose. In this study we review post-release evaluations of weed biocontrol programmes in South Africa that have been published in the last ten years, discuss the different ways these evaluations have been conducted, and identify gaps for future research. Post-release evaluations have been conducted at different scales, including physiological changes within individual plants, plant growth parameters, plant population dynamics and landscape level changes. In most cases, the results of these studies indicated that biocontrol has reduced invasions according to these metrics. While the reduction in the invasion is assumed to alleviate negative ecological and socio-economic impacts, this is usually not directly measured. Evaluations of the socio-economic and ecosystem level benefits of biocontrol were limited to just a few examples on aquatic weeds. More studies that investigate the landscape, socio-economic and ecosystem level changes due to biocontrol are required, especially for terrestrial weeds, if the true scale of the benefits provided by biocontrol are to be understood.

Short-term effects of macrophyte removal on aquatic biodiversity in rivers and lakes - Benjamin Misteli; Alexandrine Pannard; Eirin Aasland; Sarah Faye Harpenslager; Samuel Motitsoe; Kirstine Thiemer; Stéphanie Llopis; Julie Coetzee; Sabine Hilt; Jan Köhler; Susanne C. Schneider; Christophe Piscart; et al. (Journal of Environmental Management, 2023)

Trophic interactions and food web structure of aquatic macroinvertebrate communities in afromontane wetlands: the influence of hydroperiod - Nonkazimulo D. Mdidimba; Musa C. Mlambo; Samuel N. Motitsoe (Aquatic Sciences, 2021)